Pengaruh suplementasi Î²-carotene terhadap kadar glukosa darah dan kadar malondialdehida pada tikus sprague dawley yang diinduksi Streptozotocin - Soviana, Elida; Rachmawati, Banundari; Widyastiti, Nyoman Suci (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background : Hyperglycemia on diabetes mellitus can cause increasing of free radicals production. Free radicals caused lipid peroxidation reaction by forming malondialdehyde (MDA). Î²-carotene has antioxidant activity may inhibit the formation of ROS.Objective : To prove the effect of multilevel doses Î²-carotene 1 mg/kg BW, 20 mg/kg BW and 20 mg/kg BW on alternate days within 30 days orally supplementation on blood glucose level and MDA level on Sprague Dawley male rats induced by streptozotocin (STZ). Methods : Thirty rats were randomly divided into 5 groups: X1=Negative control/diabetic, X2 (STZ 40 mg/kg BW + BC 1 mg/kg BW), X3 (STZ 40 mg/kg BW + BC 10mg/kg BW), X4 (STZ 40 mg/kg BW + BC 20 mg/kg BW), X5 (technic control/non diabetic). Î²-Carotene supplementation was given by nasogastric tube on alternate days within thirty days. Blood glucose level was measured by GOD-PAP and MDA level by ELISA with TBARS methods. Data was analized using paired t-test, wilcoxon, one way anova and post hoc bonferroni. Results : there was a significant difference of blood glucose level (p = 0,0001) and MDA level (p = 0,0001) after suplementation Î²-carotene on alternate days within 30 days orally. Î²-carotene 10 mg/kg BW was the most effective and efficient dose to lowering blood glucose, while 20 mg/kg BW to lowering MDA level. Conclusion : The multilevel doses Î²-carotene (1 mg/kg BW, 10 mg/kg BW and 20 mg/kg BW) on alternate days within 30 days orally supplementation can decrease blood glucose and MDA level. Î²-carotene 10 mg/kg BW is the most effecetive and efficient to decrease blood glucose and Î²-carotene 20 mg/kg BW to decrease MDA level.